Frameshift mutation hotspot identified in Smith-Magenis syndrome: case report and review of literature - Dudding Tracy; Truong Hoa T; Blanchard Christopher L; Elsea Sarah H (BMC, 2010)
Abstract Smith-Magenis syndrome (SMS) is a complex syndrome involving intellectual disabilities, sleep disturbance, behavioural problems, and a variety of craniofacial, skeletal, and visceral anomalies. While the majority of SMS cases harbor an ~3.5 Mb common deletion on 17p11.2 that encompasses the retinoic acid induced-1 (RAI1) gene, some patients carry small intragenic deletions or point mutations in RAI1. We present data on two cases of Smith-Magenis syndrome with mutation of RAI1. Both cases are phenotypically consistent with SMS and RAI1 mutation but also have other anomalies not previously reported in SMS, including spontaneous pneumothoraces. These cases also illustrate variability in the SMS phenotype not previously shown for RAI1 mutation cases, including hearing loss, absence of self-abusive behaviours, and mild global delays. Sequencing of RAI1 revealed mutation of the same heptameric C-tract (CCCCCCC) in exon 3 in both cases (c.3103delC one case and and c.3103insC in the other), resulting in frameshift mutations. Of the seven reported frameshift mutations occurring in poly C-tracts in RAI1, four cases (~57%) occur at this heptameric C-tract. Collectively, these results indicate that this heptameric C-tract is a preferential hotspot for single nucleotide insertion/deletions (SNindels) and therefore, should be considered a primary target for analysis in patients suspected for mutations in RAI1. We expect that as more patients are sequenced for mutations in RAI1, the incidence of frameshift mutations in this hotspot will become more evident.